Analysis of Factors Affercting Employee Work Competence in the Field of Employee Mutations at the Personnel Agency and Human Resources Development of the Riau Islands Province - Putra, Hendra Eka (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
This research aims to analyze the factors that influence the work competence of employees in the Transfer, Rank and Promotion Sector of the Regional Civil Service Agency and KORPRI Riau Islands Province. So this research focuses on the essence of the factors that influence employee work competence, namely, education, experience, skills, expertise and creativity. This research is descriptive qualitative in nature with data collection techniques in the form of interviews and observations. By using theories from experts who argue that there are several factors that influence work competence, namely, the educational environment. The level of education and training received by employees can influence their work competence. Apart from that, extensive and varied work experience can help employees in dealing with complex problems or situations. Employee motivation is also needed because they tend to work better and produce better results. The skills possessed by employees can improve the quality and productivity of work, as well as ensure that the tasks given can be completed well and on time. The expertise factor has a very big influence on employee competence. This is because the expertise factor includes the knowledge, skills and work experience possessed by employees. The higher the employee's expertise, the better the employee's competence. A high creativity factor can increase employees' ability to solve problems, generate new ideas, and adapt to environmental changes. Creativity is the ability to produce innovative new ideas, creative solutions to problems, and the ability to adapt to environmental changes.